Socioeconomic factors influencing dependence of households on non-timber forest products in South Nandi Forest, Kenya - Maua, James O.; Tsingalia, Harrison Mugatsia; Cheboiwo, Joshua (Journal of Economics and Sustainable Development, 2018)
Forests are some of the key natural assets that provide a wide range of goods and services to forest adjacent communities. However, there is inadequate information on the factors that influence community members’ level of dependence on forest resources. This study examined and analyzed factors that influence dependence of households on non-timber forest products from South Nandi forest, Kenya. 431 household heads from 9 villages were interviewed using proportional random sampling in May to August 2016. Descriptive statistics and logistic regression was used to analyze the data. Results clearly indicated that 90% of the household heads obtained NTFPs from the forest pointing to the importance of this forest to the households. Twelve variables were significantly associated with dependence on the forest. These included locations of the village from the forest, time spent by household to get NTFPs, membership in CFA and ethnic groupings. The logistic regression results revealed that age, occupation of household head and distance to the market were positively and significantly correlated with dependence on NTFPs. On the other hand, years of formal education, land size, and distance to the forest were negatively and significantly correlated with dependence on NTFPs. In order to utilize NTFPs in a sustainable way, development of management plans and strategies should incorporate the socioeconomic factors.
Keywords: Socioeconomic factors; NTFPs; dependence; households; South Nandi forest